Making microchips : policy, globalization, and economic restructuring in the semiconductor industry - Mazurek, Jan (Massachusetts : The MIT Press, 1999)
Smaller, faster, better, 21. -- Hitting a moving target, 47. -- Real men have favs, 89. -- Environmental challenges of restructuring, 113. -- Cleaner, cheaper, smater?, 151. -- The XL file, 167. -- Silicon evolution, 199